Agricultural R&D in Central America: Policy, investments and institutional profile - Stads, Gert-Jan; Hartwich, Frank; Rodríguez, David; Enciso, Francisco (International Food Policy Research Institute, 2008)
Drawing from comprehensive datasets derived from primary surveys, this report reviews the major institutional developments and investment and human resource trends in public agricultural research and development (R&D) in the seven countries that constitute Central America: Belize, Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua, and Panama. A high degree of diversity exists with regard to Central America's agricultural R&D efforts. The size of the national-level R&D systems varies largely in terms of number of research staff, ranging from just 17 fte research staff in Belize to 283 in Costa Rica. Average degree levels of agricultural research staff also diverged widely from one country to the next. In El Salvador, only 1 out of every 5 agricultural scientists holds postgraduate degrees, while in Belize, Nicaragua, and Costa Rica, more than 50 percent of all agricultural research staff were trained to the MSc or PhD level. Distribution of spending among countries in the Central American region is very uneven, with Costa Rica and Nicaragua accounting for the lion's share of the region's agricultural research expenditures. Total agricultural R&D spending has remained fairly stagnant since the early 1980s. Growth in spending in Costa Rica and Belize during 1981-2006 was offset by cuts in Guatemala and El Salvador. Funding for agricultural research is still predominantly through government allocations in Panama and El Salvador. Agricultural R&D in Nicaragua, on the other hand, is extremely dependent on foreign donor funding. A number of countries have sought to fund agricultural R&D by a tax on agricultural production or exports while other countries have been successful in commercializing their research results.